17.x- [-16.x-37] =2.x+43
TÌM X
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(17.x-\left(-16.x-37\right)=2.x+37\)
\(17x+16x+37=2x+37\)
\(33x+37=2x+37\)
\(33x-2x=37-37\)
\(31x=0\)
\(x=0\)
Vậy \(x=0\)
d) Ta có: \(32\%-0.25:x=-\dfrac{17}{5}\)
\(\Leftrightarrow0.25:x=\dfrac{8}{25}+\dfrac{17}{5}=\dfrac{93}{25}\)
hay \(x=\dfrac{25}{372}\)
Vậy: \(x=\dfrac{25}{372}\)
e) Ta có: \(\left(x+\dfrac{1}{5}\right)^2+\dfrac{17}{25}=\dfrac{26}{25}\)
\(\Leftrightarrow\left(x+\dfrac{1}{5}\right)^2=\dfrac{9}{25}\)
\(\Leftrightarrow\left[{}\begin{matrix}x+\dfrac{1}{5}=\dfrac{3}{5}\\x+\dfrac{1}{5}=-\dfrac{3}{5}\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=\dfrac{2}{5}\\x=-\dfrac{4}{5}\end{matrix}\right.\)
Vậy: \(x\in\left\{\dfrac{2}{5};-\dfrac{4}{5}\right\}\)
f) Ta có: \(-\dfrac{32}{27}-\left(3x-\dfrac{7}{9}\right)^3=-\dfrac{24}{27}\)
\(\Leftrightarrow\left(3x-\dfrac{7}{9}\right)^3=\dfrac{-8}{27}\)
\(\Leftrightarrow3x-\dfrac{7}{9}=-\dfrac{2}{3}\)
\(\Leftrightarrow3x=\dfrac{1}{9}\)
hay \(x=\dfrac{1}{27}\)
g) Ta có: \(60\%\cdot x+0.4x+x:3=2\)
\(\Leftrightarrow\dfrac{4}{3}x=2\)
hay \(x=\dfrac{3}{2}\)
Vậy: \(x=\dfrac{3}{2}\)
h) PT \(\Leftrightarrow\left|\dfrac{20}{9}-x\right|=\dfrac{2}{9}\) \(\Rightarrow\left[{}\begin{matrix}\dfrac{20}{9}-x=\dfrac{2}{9}\\x-\dfrac{20}{9}=\dfrac{2}{9}\end{matrix}\right.\) \(\Leftrightarrow\left[{}\begin{matrix}x=2\\x=\dfrac{22}{9}\end{matrix}\right.\)
Vậy ...
i) PT \(\Leftrightarrow\dfrac{8}{5}+\dfrac{2}{5}x=\dfrac{16}{5}\) \(\Leftrightarrow\dfrac{2}{5}x=\dfrac{8}{5}\) \(\Leftrightarrow x=4\)
Vậy ...
A) x + 4 = -16
x = -16 - 4
x = -20
Vậy x = -20
b) 12- ( x - 5 ) =5.4
12 -x -5 = 20
x = 7 - 20
x = -13
Vậy x= -13
c) (-2)x - ( x - 17 ) = 34 - ( -x + 25 )
( -2 )x - x + 17 = 34 + x - 25
-3x + 17 = 11 + x
-3x - x = 11 - 17
-4x = -6
x = 1,5
Vậy x = 1,5
d) 17x - ( -16x - 37 ) = 2x + 43
17x + 16x - 2x = 43 -37
30x = 6
x = 0,2
Vậy x = 0,2
a,-2x -(x-17)=34-(-x+25)
-2x-x+17=34+x-25
-3x+17=9+x
-3x-x=9-17
-4x=-8
-->4x=8
x=8:4
x=2
Vậy x=2
b,17-(16x-37)=2x+43
17-16x+37=2x+43
20-16x=2x+43
-16x-2x=43-20
-18x=23
x=23:(-18)
x=23/-18
Mà x là số nguyên nên --> x thuộc tập rỗng
c,-2x-3.(x-17)=34-2(-x+25)
-2x-3x+51=34-2.(-x)-25
-5x+51=9-(-2).x
-5x+(-2).x=9-51
-7x=-42
7x=42
x=42:7
x=6
Vậy x=6
a) \(\dfrac{25}{37}\times\dfrac{18}{29}+\dfrac{18}{29}\times\dfrac{12}{37}\)
\(=\dfrac{18}{29}\times\left(\dfrac{25}{37}+\dfrac{12}{37}\right)\)
\(=\dfrac{18}{29}\times\dfrac{37}{37}\)
\(=\dfrac{18}{29}\times1\)
\(=\dfrac{18}{29}\)
b) \(\dfrac{31}{85}\times\dfrac{11}{19}+\dfrac{31}{85}\times\dfrac{12}{19}-\dfrac{42}{19}\times\dfrac{31}{85}\)
\(=\dfrac{31}{85}\times\left(\dfrac{11}{19}+\dfrac{12}{19}-\dfrac{42}{19}\right)\)
\(=\dfrac{31}{85}\times\dfrac{-19}{19}\)
\(=\dfrac{31}{85}\times-1\)
\(=-\dfrac{31}{85}\)
c) \(\dfrac{16}{53}:\dfrac{17}{9}-\dfrac{16}{53}:\dfrac{17}{8}\)
\(=\dfrac{16}{53}:\left(\dfrac{9}{17}-\dfrac{8}{17}\right)\)
\(=\dfrac{16}{53}:\dfrac{1}{17}\)
\(=\dfrac{16}{901}\)
c) \(\dfrac{1}{5}\times\dfrac{12}{31}\times\dfrac{4}{3}+\dfrac{19}{31}\times\dfrac{4}{15}\)
\(=\dfrac{4}{15}\times\dfrac{12}{31}+\dfrac{19}{31}\times\dfrac{4}{15}\)
\(=\dfrac{4}{15}\times\left(\dfrac{12}{31}+\dfrac{19}{31}\right)\)
\(=\dfrac{4}{15}\times\dfrac{31}{31}\)
\(=\dfrac{4}{15}\times1\)
\(=\dfrac{4}{15}\)
a: =18/29*(25/37+12/37)
=18/29
b: =31/85(11/19+12/19-42/19)
=-31/85
c; =16/53(9/17+8/17)=16/53
d: =4/15(12/31+19/31)=4/15
\(\frac{7}{5}+\left(\frac{2\left(\frac{1}{7}+\frac{1}{17}+\frac{1}{37}\right)}{5\left(\frac{1}{7}+\frac{1}{17}+\frac{1}{37}\right)}\right)\cdot x=\frac{16}{5}\)
\(\frac{2}{5}x=\frac{16}{5}-\frac{7}{5}\)
\(\frac{2}{5}x=\frac{9}{5}\)
x = \(\frac{9}{5}:\frac{2}{5}\)
x = 9/2
\(1\frac{2}{5}+\left(\frac{\frac{2}{7}+\frac{2}{17}+\frac{2}{37}}{\frac{5}{7}+\frac{5}{17}+\frac{5}{37}}\right).x=\frac{16}{5}\)
\(\frac{7}{5}+\left[\frac{2.\left(\frac{1}{7}+\frac{1}{17}+\frac{1}{37}\right)}{5.\left(\frac{1}{7}+\frac{1}{17}+\frac{1}{37}\right)}\right].x=\frac{16}{5}\)
\(\frac{7}{5}+\frac{2}{5}.x=\frac{16}{5}\)
\(\frac{2}{5}.x=\frac{16}{5}-\frac{7}{5}\)
\(\frac{2}{5}.x=\frac{9}{5}\)
\(x=\frac{9}{5}:\frac{2}{5}\)
\(x=\frac{9}{5}.\frac{5}{2}\)
\(x=\frac{9}{2}\)
\(1\frac{3}{5}+\left(\frac{\frac{2}{7}+\frac{2}{17}+\frac{2}{37}}{\frac{5}{7}+\frac{5}{17}+\frac{5}{37}}\right)x=\frac{16}{5}\)
\(\Rightarrow\frac{2\left(\frac{1}{7}+\frac{1}{17}+\frac{1}{37}\right)}{5\left(\frac{1}{7}+\frac{1}{17}+\frac{1}{37}\right)}.x=\frac{16}{5}-\frac{8}{5}\)
\(\Rightarrow\frac{2}{5}.x=\frac{8}{5}\)
\(\Rightarrow x=\frac{8}{5}:\frac{2}{5}=4\)
vậy x=4
=.8/5+((2*17*37+2*7*37+2*7*17)/(7*17*37))/((5*17*37+5*7*37+5*7*17)/(7*17*37))*x=16/5
=>8/5+((2*17*37+2*7*37+2*7*17)/(7*17*37))*((7*17*37)/(5*17*37+5*7*37+5*7*17))*x=16/5
=>8/5+(2(17*37+7*37+7*17))/(5(17*37+7*37+7*17))*x=16/5
=>8/5+(2/5)*x=16/5
=>(2/5)*x=16/5-8/5
=>(2/5)*x=8/5
=>x=(8/5)/(2/5)
=>x=4
Vậy x=4
\(\frac{x+15}{35}+\frac{x+16}{36}=\frac{x+17}{37}+\frac{x+18}{38}\)
\(\frac{x+15}{35}-1+\frac{x+16}{36}-1=\frac{x+17}{37}-1+\frac{x+18}{38}-1\)
\(\frac{x-20}{35}+\frac{x-20}{36}-\frac{x-20}{37}-\frac{x-20}{38}=0\)
\(\left(x-20\right)\left(\frac{1}{35}+\frac{1}{36}-\frac{1}{37}-\frac{1}{38}\right)=0\)
\(\Rightarrow x-20=0\Rightarrow x=20\)
Vậy x=20
\(\frac{x+15}{35}+\frac{x+16}{36}=\frac{x+17}{37}+\frac{x+18}{38}\)
\(\Leftrightarrow\frac{x+15}{35}.885780+\frac{x+16}{36}.885780=\frac{x+17}{37}.885780+\frac{x+18}{38}.885780\)
\(\Leftrightarrow25308\left(x+15\right)+24605\left(x+16\right)=23940\left(x+17\right)+23310\left(x+18\right)\)
\(\Leftrightarrow49913x+773300=47250x+826560\)
\(\Leftrightarrow49913x=47250x+53260\)
\(\Leftrightarrow49913x-47250x=47250x+53260-47250x\)
\(\Leftrightarrow2663x=53260\)
\(\Leftrightarrow x=20\)
\(\Rightarrow x=20\)
<=> 17x + 16x + 37 = 2x + 43
<=> 17x + 16x - 2x = 43 - 37
<=> 31x = 6
<=> x = 6 : 31
<=> x = 6/31